Nitrous oxide production and consumption by marine ammonia-oxidizing archaea under oxygen depletion - Hernández-Magaña, Elisa; Kraft, Beate (Frontiers in Microbiology, 2024)
Ammonia-oxidizing archaea (AOA) are key players in the nitrogen cycle and among the most abundant microorganisms in the ocean, thriving even in oxygen-depleted ecosystems. AOA produce the greenhouse gas N2O as a byproduct of ammonia oxidation. Additionally, the recent discovery of a nitric oxide dismutation pathway in the AOA isolate Nitrosopumilus maritimus points towards other N2O production and consumption pathways in AOA. AOA, which perform NO-dismutation when exposed to oxygen depletion, produce oxygen and dinitrogen as final products. Based on the transient accumulation of N2O coupled to oxygen accumulation, N2O was proposed as intermediate in this novel archaeal pathway. In this study, we spiked N2O to oxygen-depleted incubations with pure cultures of two marine AOA isolates, that were performing NO-dismutation. By using combinations of N compounds with different isotopic signature ( 15 NO2 -pool + 44 N2O spike; 14 NO2 -pool + 46 N2O spike), we evaluated the N2O spike effects on the production of oxygen and on the isotopic signature of N2 and N2O. The experiments confirmed that N2O is an intermediate in NO-dismutation by AOA distinguishing it from similar pathways in other microbial clades. Furthermore, we show that AOA rapidly reduce high concentrations of spiked N2O to N2. These findings advance our understanding of microbial N2O production and consumption in oxygen-depleted settings and highlight AOA as potentially important key players in N2O turnover.